NMR-Based Characterization of Phenothiazines as a RNA Binding Scaffold - Mayer, Moriz; James, Thomas L (Journal of the American Chemical Society, 2004)
Phenothiazines were identified by virtual screening as promising ligands for HIV-1 TAR RNA and A-site ribosomal RNA, and binding in each case was verified experimentally. Consequently, since phenothiazines generally possess high bioavailability and low toxicity, we used several NMR techniques to explore the binding characteristics of acetopromazine with a total of five different RNA constructs:  four as potential drug targets plus one control RNA construct. Acetopromazine was able to bind to various internal bulges and terminal loops containing both purines and pyrimidines, but no binding could be detected with double-stranded RNA or tetraloops. Dissociation constants determined via NMR varied from 0.27 to >3 mM. Analysis of differential saturation transfer difference (STD) NMR effects of acetopromazine suggests that the phenothiazine moiety has the closest contact to the binding sites of TAR and A-site RNA while the flexible N,N-dimethylpropylamino side chain contributes less to binding. NMR studies on A-site ribosomal RNA binding by six commercially available phenothiazines, while too few to establish a true structure−activity relationship, revealed a distinct dependence on aromatic ring and side chain substituents. Substituted phenothiazines have low molecular weight, are not highly charged, and have an inherent affinity for irregular tertiary RNA folds, suggesting that they can serve as a novel scaffold for constructing RNA-binding ligands.